Sympathetic-neuron-derived neuropeptide Y (NPY) regulates adipose tissue immunometabolic homeostasis - Zhu, Y (2024)
Neuropeptide Y (NPY) is secreted by sympathetic nerves (LUNDBERG et al.,1982; Lundberg, Franco-Cereceda, Hemsen, Lacroix, & Pernow, 1990), but its direct impact on thermogenic adipocytes is unknown. Here we uncover the mechanism by which peripheral NPY protects from obesity. Our imaging of cleared murine brown and white adipose tissue (BAT and WAT) established that NPY+ sympathetic axons are only a minority that mostly maps to the peri-vasculature; our analysis of single-cell RNA-sequencing datasets identifies mural cells as the main NPY-responsive cells in adipose tissues. We show that NPY sustains mural cells, known as a source of beige cells in both BAT and WAT (Long et al., 2014; Shamsi et al., 2021) and that NPY facilitates the differentiation to thermogenic adipocytes. We found that diet-induced obesity leads to neuropathy of NPY+ axons and concomitant depletion of the mural cell pool of beige fat progenitors. This defect is replicated in conditional knockout (cKO) mice with NPY specifically abrogated from sympathetic neurons. These cKO mice have whitened BAT with reduced thermogenic ability and lower energy expenditure even before the onset of obesity; they develop adult-onset obesity on a regular chow diet and are more susceptible to diet-induced obesity without increasing food consumption. Our results indicate that relative to central NPY, peripheral NPY produced by the sympathetic nerves has the opposite effect on body weight homeostasis by sustaining the proliferation of the mural cell progenitors of thermogenic adipocytes.